The potential role of next-generation sequencing in identifying MET amplification and disclosing resistance mechanisms in NSCLC patients with osimertinib resistance - Xiao, Xiao; Xu, Ren; Lu, Jun; Xin, Beibei; Wang, Chenyang; Zhu, Kexin (Frontiers in Oncology, 2024)
PurposesOsimertinib, one of the third-generation EGFR-tyrosine kinase inhibitors (TKIs) designed to target EGFR T790M mutation, significantly improves the prognosis of lung cancer. However, drug resistance still happens and MET amplification is responsible for one of the main causes. Fluorescence in situ hybridization (FISH) is the gold standard for MET amplification detection, but fundamentally limited by observer subjectivity. Herein, we assessed the value of next-generation sequencing (NGS) method in MET amplification detection in non-small cell lung cancer (NSCLC), as well as revealed the mutation profiling of NSCLC patients with osimertinib resistance to provide some valuable clues to the mechanisms of resistance.MethodsA total of 317 cancer tissue samples from 317 NSCLC patients at time of progression following osimertinib were submitted to NGS and only 96 tissues were tested by FISH simultaneously. With FISH results as gold standard, enumeration algorithm was applied to establish the optimal model for identifying MET amplification using gene copy number (GCN) data.ResultsThe optimal model for identifying MET amplification was constructed based on the GCN of MET, BRAF, CDK6 and CYP3A4, which achieved a 74.0% overall agreement with FISH and performed well in identifying MET amplification except polysomy with a sensitivity of 85.7% and a specificity of 93.9%. The inconsistency between NGS and FISH occurred mainly in polysomy subtype, while MET GCN ≥ 5 could be reliably recognized by NGS. Moreover, the most frequently mutated genes in NSCLC patients with osimertinib resistance were EGFR (59.94%), followed by TP53 (43.85%), NRG1 (9.46%), PIK3CA (6.31%), and ATM (5.36%). The known resistance mechanisms, including MET amplification, EGFR (C797S, L718Q/R), TP53, CDK4, CDK6, CDKN2A, BRAF, KRAS, NRAS and PIK3CA mutations were also disclosed in our cohort.ConclusionsNGS assay can achieve a high concordance with FISH in MET amplification detection and has advantages in portraying various genetic alterations, which is of worthy in clinical promotion.